GOOD GOVERNANCE DALAM PERSPEKTIF ETIKA BIROKRASI MENUJU TERWUJUDNYA PERILAKU APARATUR YANG BERSIH DAN BEBAS KKN - Satibi, Iwan (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
This article describes the importance of implementing good governance in ethical perspectives related to apparatus behavior as part of creating a government that is clean free from corruption, collusion and nepotism. Good governance is a must that can not be bargained anymore, therefore political will from various parties, especially the government to realize the concept needs encouragement and support from all elements of the nation. In another position, the nation's deterioration caused by the